Sex differences in skin microvascular structure and function in persons with newly diagnosed hypertension - A. A. Fedorovich; A. Yu. Gorshkov; A. I. Korolev; K. V. Omelyanenko; V. A. Dadaeva; M. A. Mikhailova; M. G. Chashchin; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To determine sex differences in the structural and functional state of skin microcirculation in individuals with newly diagnosed hypertension.Material and methods. The study included 124 men and 42 women of working age with low or moderate cardiovascular risk and newly diagnosed hypertension. Skin microcirculation was examined on the left upper limb simultaneously by three methods: 1) video capillaroscopy; 2) laser Doppler flowmetry; 3) photoplethysmography.Results. According to video capillaroscopy, in men compared to women, the functional and structural capillary density is lower — 79 vs 89 cap/mm2 (p<0,05) and 109 vs 128 cap/mm2 (p<0,0005), respectively, while pericapillary area size and functional/structural capillary density ratio are higher 109 vs 97 µm (p<0,005) and 0,75 vs 0,70 (p<0,005), respectively. Laser Doppler flowmetry of middle finger skin in men revealed higher level of tissue perfusion (18,42 vs 16,35 perfusion units (pf), p<0,05), the contribution to the total spectral power of reflected endothelial signal (24,77 vs 16,32%, p<0,01) and neurogenic (25,92 vs 18,21%, p<0,05) mechanisms of microcirculation regulation, the level of constrictor reaction of microvessels during the respiratory test (50 vs 33%, p<0,05, 0001). Women had higher endothelial tone (2,63 vs 2,21 pF (p<0,01)), neurogenic tone (2,39 vs 2,12 pF (p<0,05)), intravascular resistance (0,78 vs, 0,65 pF p<0,05)) and post-occlusive reactive hyperemia (123,5 vs 112,5% (p<0,05)). According to photoplethysmography, the normalized augmentation index in men is lower than in women — 5,6 vs 16,8% (p<0,0001).Conclusion. Women, despite the greater capillary density, have a lower level of tissue perfusion, higher tone of the endothelial and neurogenic mechanisms of microcirculation regulation, higher intravascular resistance. The constrictor reaction of skin microvessels in women is lower, while the dilator reserve and augmentation index are higher.